The philosophy of the stoics and its effect in the philosophy of education (Journal of Hama University, 2021)
The research aimed to introduce the stoics, explain and analyze their philosophy, which consists of three parts: knowledge, nature and ethics.In knowledge, the stoics represented a sensory theory. They also defined the degrees and resources of knowledge, the certainty standards and the theory of logic.In nature, they represented a theory, which aimed to define the universe, its raise, formation and life cycle. They also defined the human soul, its relationship with the body and its roles. The stoics also represented their opinions about the lord, they belived in a single lord who looks after the world and organize it.In ethics, the stoics demonstrated that ethics can be fulfilled by meeting the nature requirements – the reason requirements -. They also represented their thoughts about happiness, virtue, goodness and evil. They also defined the duty ethics and the characteristics of the stoic sage. Finally, they believed in cosmobilism.The stoics left numerous effects in philosophy of education. They represented a knowledge theory based on senses dependence to get knowledge, reason dependence in life and ethics formation. They focused on physics for its role in the discovery of the nature’s laws and utilizing it to serve ethics. They demonstrated that lord is the brain, which created the entity, looks after it and directs it. They set up ethics based on reason. They demonstrated virtue as the extreme goodness and the aim of virtue is to live calm and peacefully and to make human resist desires and emotions and which deprive him of happiness.